(untitled) (Conferencea, 2022)
It is necessary to adopt a separate government decision to expand the holding of export fairs for industrial enterprises and other industries that produce competitive products in our country, as well as to widely use modern methods of product sales, to attract our main manufacturers to prestigious international fairs to present their products and conclude new export contracts.